Women’s Equality in Islamic Teachings Seen Through the Perspective of Fair and Civilized Humanity (Kemanusiaan Yang Adil Dan Beradab) - Jirzanah Jirzanah; Budisutrisna Budisutrisna (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2023)
The Islamic vision of women’s equality challenges the view of patriarchal ideology that has been established in the culture of society in various parts of the world. It is important to analyze Islamic teachings regarding women’s equality through the philosophical meaning of a fair and civilized humanity principle. Philosophical analysis produces a paradigmatic and universal understanding. The problem studied is the description of Islamic teachings regarding women’s equality and the analysis results are reviewed from the perspective of a fair and civilized humanity. The aim is to obtain a paradigmatic and universal concept of gender equality. The analysis uses the method of philosophical hermeneutics, through the stages of understanding, interpretation, description, internal coherence, and holistic analysis. The study results show that Islam teaches the position of women to be equal in gender relations, that is, not to demean, not indulge, nor to equate (blurred emancipation) between men and women. The humanity taught by Islam and the second precept of Pancasila is the same, that is, it is based on the nature of human nature. Humanity taught by Islam and the second precept of Pancasila do not differentiate between gender, social status, religious affiliation, ethnic background and race in the contexts of life. Men and women are components together in humanity, because men and women are responsible for realizing fair, civilized and democratic relations.